Meningkatkan Keputusan Pembelian Annaba’s Cookies Melalui Electronic Word of Mouth - Annaba Salamah; Parlagutan Silitonga (CV. Multi Kreasi Media, 2023)
Micro-enterprises have limited resources in choosing strategic places and high-cost promotions. For this reason, efforts are needed with the minimum possible cost of introducing and providing information to potential buyers, The purchase decision of a product is one of the first strategies companies need to use in creating a good first impression on a purchase. Because a good impression will create customer satisfaction even to customer loyalty. This study aims to improve purchasing decisions mediated by Electronic Word of Mouth (E-WoM) based on product quality factors and price perception. The method used in the study is the survey method using SmartPLS 3.0 and the data processing using PLS-SEM Path Analysis. The population and sample used were the total of Annaba’s Cookies consumers as many as 184 respondents through accidental sampling technique. The results of this study state that all variables have a positive and significant influence both direct and indirect influences